Influence of X-Ray Irradiation During Photoemission Studies on Halide Perovskite-Based Devices - Ralaiarisoa, Maryline; Frisch, Johannes; Frégnaux, Mathieu; Cacovich, Stefania; Yaïche, Armelle; Rousset, Jean; Gorgoi, Mihaela; Ceratti, Davide R.; Kodalle, Tim; Roncoroni, Fabrice; Guillemoles, Jean François; Etcheberry, Arnaud; et al. (Small Methods, 2023)
Metal halide perovskites (MHPs) are semiconductors with promising application in optoelectronic devices, particularly, in solar cell technologies. The chemical and electronic properties of MHPs at the surface and interfaces with adjacent layers dictate charge transfer within stacked devices and ultimately the efficiency of the latter. X-ray photoelectron spectroscopy is a powerful tool to characterize these material properties. However, the X-ray radiation itself can potentially affect the MHP and therefore jeopardize the reliability of the obtained information. In this work, the effect of X-ray irradiation is assessed on Cs0.05MA0.15FA0.8Pb(I0.85Br0.15)3 (MA for CH3NH3, and FA for CH2(NH2)2) MHP thin-film samples in a half-cell device. There is a comparison of measurements acquired with synchrotron radiation and a conventional laboratory source for different times. Changes in composition and core levels binding energies are observed in both cases, indicating a modification of the chemical and electronic properties. The results suggest that changes observed over minutes with highly brilliant synchrotron radiation are likely occurring over hours when working with a lab-based source providing a lower photon flux. The possible degradation pathways are discussed, supported by steady-state photoluminescence analysis. The work stresses the importance of beam effect assessment at the beginning of XPS experiments of MHP samples.
CRIS-Team Scopus Importer:2023-09-22
Keywords: beam; damage; devices; flux; perovskites; photoelectron spectroscopy; X-ray